Kesantunan Imperatif dalam Proses Pembelajaran di Magister Pendidikan Bahasa Indonesia Program Pasca Sarjana Universitas Mataram - Siti Djuwarijah (LPPM Universitas Bumigora Mataram, 2017)
Language functionate as interaction means in various fields, one of them is the education field. Education as part of the teaching in the learning process. Thus language as a means of communication, teaching and learning process occur an interaction between lecturer ad learners in the education field. In this case, the educator is a lecturer and the students are college students. In interacting, involves norms of verbal and non verbal behavior. Verbal behavior manifested in the form of invitations, orders, until prohibition on learners. Verbal imperative will differ based on the background of the educator and the learner. In this study, the writer describes the form of imperative sentences generated by educators at the Master's Degree in Indonesia Language Education Class at Mataram University and the level of politeness. This research used qualitative and quantitative data. The method used in this research is listening with basic techniques tapping and notes taking, The results of the analysis are presented by formal and informal methods, while the theory used is speech act